NON-INTEREST INCOME AND BANKING INTERMEDIATION IN ASIAN COUNTRIES - Hasbi Almegayana Atmawidjaya; Chaikal Nuryakin (SEAN Institute, 2023)
Bank has a vital role as an intermediary institution that can encourage economic growth in countries. However, many banks have started expanding non-interest income activity based on income from fees. This study discusses the factors associated with non-interest income, especially during the banking digitalization era. Banks may rely on non-interest income in dire economic conditions when credit demand drops. However, if banks continue to rely on non-interest income in good economic conditions, they hamper their intermediation function. Therefore, it is essential to know the association between loan to deposit ratio (LDR) as a proxy of intermediation function with non-interest income in good economic and dire economic conditions. This study uses panel data with fixed effect model regression on banks from 10 Asian countries. The estimation result shows that the loan to deposit ratio is negatively correlated with non-interest income in good and dire economic conditions. Thus, there is an indication that banks have more and more shifting to non-intermediation services.